Condition of Danube flotilla between Russian-Turkish wars of the XIX century as mobilization to the next war - А. О. Verbovoy (Вестник Самарского университета: История, педагогика, филология)
The article examines the problems of the Russian-Turkish wars waged by Russia in the XIX century, especially the use of such a unit as the Danube River Flotilla. Particular emphasis is placed on preparations for the next war with Turkey, namely, the maintenance and preparation of the river unit for the next military conflict. The work also emphasizes that the maintenance of the Danube Flotilla as a unit in peacetime meant preparation for war in the very near future. On the other hand, failure to disband the river flotilla after another war with Turkey meant that the main causes of the conflict had not been fully resolved and, as a consequence, preparation for the next war. At the same time, in all cases, at the stage of preparation for the next war with Turkey, Russia made statements that no preparations were being made for the next war, but when the Turkish side proposed resolving the issue peacefully, such proposals were rejected by the Russian government and the emperor. This led to another Russian-Turkish war with the use of the Danube Flotilla. Thus, the maintenance and strengthening of the Danube Flotilla throughout the XIX century meant that there would soon be another Russian-Turkish war. The only exceptions were the Russian-Turkish War of 1806–1812 and the Russian-Turkish War of 1877–1878, when the Danube Flotilla was created specifically to participate in them. The reasons for each of the Russian-Turkish wars were slightly different, but the following always remained: protectorate over the Balkan and Danube countries, and, starting with the Crimean War, also the capture of Istanbul, the installation of a cross over Hagia Sophia and control over the Bosphorus and the Dardanelles straits.